PREDIKSI EROSI TANAH DI AREAL REHABILITASI DAERAH ALIRAN SUNGAI DESA BANTIK KABUPATEN BOLAANG MONGONDOW - Fajar Gemilang Sahman; Joshephus I. Kalangi; Johan A. Rombang (Universitas Sam Ratulangi, 2021)
Watersheds have some important roles for life in the vicinity, such as storing rainwater and flowing it as a water source. Disturbances in watersheds can causes soil erosion, which also causes the loss of fertile soil layers and carries solids and chemicals that can harm agricultural and human activities. Erosion prediction can be done by using the RUSLE method. The purpose of this study is to determine the rate of erosion in the rehabilitation area of the Bantik’s watershed. The result of this study is to indicate that the erosion in the rehabilitation area of the Bantik’s watershed is dominate by very light erosion with the lowest value around 1.04 tons/ha/yr and the highest value around 81.02 tons/ha/yr. It is necessary to take conservation measures on the soil and slopes so that erosion does not exceed its natural limits.